A surface plasmon resonance assay for characterisation and epitope mapping of anti‐GLP‐1 antibodies. Issue 8 (19th April 2018) - Thomsen, Lasse; Gurevich, Leonid
Abstract: The incretin hormone glucagon‐like peptide‐1 (GLP‐1) has been subject to substantial pharmaceutical research regarding the treatment of type 2 diabetes mellitus. However, quantification of GLP‐1 levels remains complicated due to the low circulation concentration and concurrent existence of numerous metabolites, homologous peptides, and potentially introduced GLP‐1 receptor agonists. Surface plasmon resonance (SPR) facilitates real‐time monitoring allowing a more detailed characterisation of the interaction compared with conventional enzyme‐linked immunosorbent assays (ELISA). In this paper, we describe the development of the first SPR assays for characterisation of anti‐GLP‐1 antibodies for ELISA purposes. Binding responses were obtained on covalently immobilised anti‐GLP‐1 antibodies at 12°C, 25°C, and 40°C and fitted to a biomolecular (1:1) interaction model showing association rates of 1.01 × 10 3 to 4.54 × 10 3 M −1 s −1 and dissociation rates of 3.56 × 10 −5 to 1.56 × 10 −3 s −1 leading to affinities of 35.2 to 344 nM, depending on the temperature. Determination of thermodynamic properties revealed an enthalpy driven interaction (ΔH < ΔS < 0) with higher affinities at lower temperatures due to the formation and stabilisation of hydrogen bonds within the binding site primarily composed of polar amino acids (ΔCp < 0). Pair‐wise epitope mapping was performed on captured anti‐GLP‐1 antibodies followed by subsequent interaction with GLP‐1 (7‐36) and other anti‐GLP‐1 antibodies. A global evaluation of every binding response led to an epitope map elucidating the potential of various anti‐GLP‐1 antibody pairs for sandwich ELISA and hence pinpointing the optimal antibody combinations. The SPR assays proved capable of providing vital information for ELISA development endorsing it as a useful optimisation tool. Abstract : Surface plasmon resonance (SPR) is a capable tool for obtaining quantitative information on molecular interactions and hence indispensable for designing and optimizing, eg, ELISA assay. This report presents first SPR study of the interaction of incretin hormone glucagon‐like peptide‐1 (GLP‐1) with several different anti–GLP‐1 antibodies, providing data on both binding kinetics and thermodynamics of the interaction. Additionally, pairwise epitope mapping is performed to investigate the potential of several antibody pairs for sandwich ELISA.